2017
DOI: 10.1038/s41598-017-07964-5
|View full text |Cite
|
Sign up to set email alerts
|

JAM-A overexpression is related to disease progression in diffuse large B-cell lymphoma and downregulated by lenalidomide

Abstract: Cancer stem cells play an important role on tumor progression. Biomarkers of stem cell property and their relationship to extranodal involvement of malignant lymphocytes are undefined in diffuse large B-cell lymphoma (DLBCL). Here we showed that junctional adhesion molecule-A (JAM-A) was highly expressed in DLBCL patients with multiple extranodal lesions. JAM-A maintained B-lymphoma cell stemness and was associated with cell invasion and epithelial-to-mesenchymal transition both in vitro and in vivo. As mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Based on these findings and on several pieces of compelling evidence investigating how the deregulated adhesion-mediated system would contribute to more aggressive disease, several attempts uncovered the junctional adhesion molecule role in mediating disease aggressiveness [ 141 , 144 , 145 ]. In line with previous results [ 128 , 146 , 147 ], preliminary data from our lab demonstrate that direct contact of environmental cells with DLBCL cells would enhance adhesion molecule levels, thus preventing both direct and indirect cell invasiveness and epithelial–mesenchymal transition and extra-nodal dissemination (unpublished data). Even more interesting, the cell adhesion molecule junctional adhesion molecule-A (JAM-A) presents remarkable features [ 148 ], whereby it can interact with itself if expressed on two opposing cell types.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Based on these findings and on several pieces of compelling evidence investigating how the deregulated adhesion-mediated system would contribute to more aggressive disease, several attempts uncovered the junctional adhesion molecule role in mediating disease aggressiveness [ 141 , 144 , 145 ]. In line with previous results [ 128 , 146 , 147 ], preliminary data from our lab demonstrate that direct contact of environmental cells with DLBCL cells would enhance adhesion molecule levels, thus preventing both direct and indirect cell invasiveness and epithelial–mesenchymal transition and extra-nodal dissemination (unpublished data). Even more interesting, the cell adhesion molecule junctional adhesion molecule-A (JAM-A) presents remarkable features [ 148 ], whereby it can interact with itself if expressed on two opposing cell types.…”
Section: Discussionsupporting
confidence: 91%
“…Mechanistically, endothelial cells, by expressing TIM-3, HB-EGF [ 120 , 121 , 122 ], and a plethora of surface and soluble factors, prompt defective immunosurveillance and, in turn, allow for the persistence and proliferation of lymphoid neoplastic cells [ 123 , 124 , 125 ], envisioning novel therapeutic windows [ 126 , 127 ]. Moreover, the initial observation that the expression level of the adhesion molecules by the malignant lymphoma cells can predict disease outcome in extranodal DLBCL [ 128 ] prompted further investigation, especially in peculiar clinical disease phenotypes, such as DLBCLs involving the central nervous system (CNS) [ 128 ]. Remarkably, CNS spreading represents a paradigmatic extranodal localization with peculiar pathobiology involving adhesion molecule deregulated expression [ 129 ] and hyperactivation of the angiogenesis fueling pathway [ 130 ] along with a truncal genomic signature [ 131 ], which can contribute to drug sensitivity and resistance [ 132 , 133 , 134 ], as in other malignancies [ 135 , 136 , 137 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules are known to mediate leukocyte adhesion or invasion [ 17 ], and were suggested to contribute to the invasive character of PCNSMLs. A recent report showed that junctional adhesion molecule-A was highly expressed in DLBCL patients with multiple extranodal lesions, and its overexpression may trigger transforming growth factor-β/NODAL signaling, cause B-lymphoma cell aggressiveness, and promote extranodal involvement [ 18 ]. It is possible that certain adhesion molecules and/or gelatinases caused the aortic tumor formation in our present case.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [ 41 ] show that junctional adhesion molecule-A (JAM-A) was highly expressed in DLBCL patients with multiple extranodal lesions. JAM-A maintains B lymphoma cell stemness and was associated with cell invasion and epithelial-to-mesenchymal transition both in vitro and in vivo.…”
Section: Prognostic Factors In Lymphomamentioning
confidence: 99%